2022
DOI: 10.1111/cns.13854
|View full text |Cite
|
Sign up to set email alerts
|

Group‐based trajectory modeling of intracranial pressure in patients with acute brain injury: Results from multi‐center ICUs, 2008–2019

Abstract: Objective:The objective of the study was to characterize the longitudinal, dynamic intracranial pressure (ICP) trajectory in acute brain injury (ABI) patients admitted to intensive care unit (ICU) and explore whether it added sights over traditional thresholds in predicting outcomes.Methods: ABI patients with ICP monitoring were identified from two public databases named Medical Information Mart for the Intensive Care (MIMIC)-IV and eICU Collaborative Research Database (eICU-CRD). Group-based trajectory modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…A pressão intracraniana (PIC) é uma das principais preocupações em relação ao neuro crítico na unidade de terapia intensiva (UTI), segundo um estudo realizado por Yang et al (2022), foi confirmado que a hipertensão intracraniana (definida como valores de PIC superiores a 20 -25 mmHg) é considerada patologicamente relevante devido à sua relação com a mortalidade (Kharouba et al, 2023) De acordo com um estudo efetuado por Hawryluk et al (2019), bloqueadores neuromusculares (BNMs) também mostraram eficácia para redução da HIC, tendo em vista que esses interceptam a transmissão do impulso nervoso, consequentemente, inibindo os movimentos do paciente neuro crítico, pois a movimentação desse enfermo aumenta a PIC, assim como os sedativos (Midazolan, Propofol e Dexmetomidina) que visam a manutenção da hemodinâmica neuronal (BAUERSCHMIDT et al, 2023). Porém, ressaltam precauções para o uso desses fármacos, destaca-se, portanto, que a utilização precoce, rotineira e prolongada dessas substâncias em pacientes neuro críticos é prejudicial.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A pressão intracraniana (PIC) é uma das principais preocupações em relação ao neuro crítico na unidade de terapia intensiva (UTI), segundo um estudo realizado por Yang et al (2022), foi confirmado que a hipertensão intracraniana (definida como valores de PIC superiores a 20 -25 mmHg) é considerada patologicamente relevante devido à sua relação com a mortalidade (Kharouba et al, 2023) De acordo com um estudo efetuado por Hawryluk et al (2019), bloqueadores neuromusculares (BNMs) também mostraram eficácia para redução da HIC, tendo em vista que esses interceptam a transmissão do impulso nervoso, consequentemente, inibindo os movimentos do paciente neuro crítico, pois a movimentação desse enfermo aumenta a PIC, assim como os sedativos (Midazolan, Propofol e Dexmetomidina) que visam a manutenção da hemodinâmica neuronal (BAUERSCHMIDT et al, 2023). Porém, ressaltam precauções para o uso desses fármacos, destaca-se, portanto, que a utilização precoce, rotineira e prolongada dessas substâncias em pacientes neuro críticos é prejudicial.…”
Section: Discussionunclassified
“…Quando acontece uma elevação do volume de um destes conteúdos intracranianos, ocorre a Hipertensão Intracraniana (HIC), a qual deve ser tratada se insistir acima de 20 -22 mmHg. (Yang et al, 2022;Treggiari et al, 2023).…”
Section: Introductionunclassified
“…Yang et al. found that the prognosis of patients with acute brain injury was not only associated with the level of intracranial pressure at baseline, but also with dynamic changes in intracranial pressure [ 19 ]. In addition, dynamic monitoring of urine output over 24 h has been shown to be valuable in predicting AKI in septic patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even for the same patient, adjusting ideal cerebral perfusion may require arterial blood pressure (ABP) changes during periods of physiological instability following injury [ 11 , 12 ]. Hence, determining the most vulnerable periods for tissue hypoxia and cellular dysfunction [ 13 , 14 ] can be challenging [ 15 18 ]. In this context, intracranial compliance (ICC) impairment, the threshold with which intracranial volume has overpassed the inner compensatory reserve [ 19 , 20 ], can be a more reliable target than ICP alone [ 21 ].…”
Section: Introductionmentioning
confidence: 99%